Overtime Hours in American Industry - Wolfbein, Seymour L. (The Review of Economics and Statistics, 1958)
PpT HIS article is a first report on some aspects of a new program of collection on the number of overtime hours worked in industries in the manufacturing segment of the economy begun by the Department of Labor's Bureau of Labor Statistics in January I956. The Bureau of Labor Statistics has been collecting data on working hours a long time and currently publishes information on the length of the workweek in considerable industrial and geographical detail. The new program was initiated in response to the increasing attention being given to the changing length and structure of the workweek and to the need an additional sensitive indicator of current economic developments. As a major subject legislation and collective bargaining, the workweek has, of course, become a considerable element in affecting labor income and labor cost. As will be shown below, fully ten per cent of the average factory worker's paycheck in I956 was accounted by premium payments work outside the regular scheduled The workweek also has become an important mechanism short-run adjustments of labor supply and labor demand. Especially during the past I 5 years of comparatively high levels of economic activity and scarce manpower resources in many occupational fields, changing man-hour input by changing the number of hours rather than the number of men has offered considerable advantages. It has become a significant factor in current economic analysis. Recent studies show the workweek to be one of the lead series in cyclical changes. Finally, it has become an important item in projections and the building of models of future economic growth. The interactions of a decline in hours of work and increases in productivity, the impact of increasing leisure time on consumption patterns and levels are just two examples of the kinds of factors which have to be considered in any assessment of future trends. Two points should be made at the beginning of this report. First, this is a new collection program and the data so far cover only one year. Obviously, this finds various industries at different points in their seasonal cycles, at different stages in their long-run development, and, in many cases, with situations peculiar to various forces affecting the year I956. In general, this was a period of slight downturn both in employment of factory production workers and their over-all hours of work. All of this should be taken into account in assessing the data presented below. Second, the definitions employed by the BLS in its collection program on employment and hours are important to a clear understanding of the data. For information on the length of the workweek, the BLS asks the employer to report the number of hours worked or in the payroll period ending nearest the I5th of each month. The phrase paid is critical: A worker getting $2 an hour a 4o-hour week, but on vacation during the payroll week, is reported and counted at 4o hours with $8o pay. The BLS series, therefore, does not measure actual labor input or actual hours of work put in place. The definition or concept employed is nearer one of labor income (or cost) although it by no means includes all such items of income or cost. Excluded, example, are Christmas bonuses and other irregular payments to employees. For information on overtime hours the BLS asks the employer to report the number of hours for which premiums were because the hours were in excess of the number of hours of either the straight-time workday or workweek. Critical here is the word premiums. Overtime hours are counted only if a premium above the straight-time rate was whether it be extra hours during any working day, extra hours during any working week above those stipulated by the Fair Labor Standards Act or a collective bargaining agreement, work on what would otherwise be a holiday, etc. i. Although overtime averaged between 2 12 and 3 hours manufacturing as a whole in I956, there were significant and substantial differences among the various industries during the